Some Nutritional Aspects of Lasia spinosa (Kohila) - Shefana, A.G.; Ekanayake, S. (My University, 2009)
Lasia spinosa (local name - kohila) is a stout, marshy plant with a creeping spiny rhizome, The tender leaves and rhizomes are used as a vegetable and are recommended for a variety of diseases in Ayurvedic medicine, The present study was carried out to determine the total antioxidant activity of Lasia spinosa rhizome and the contribution to antioxidant activity from the polyphenol fraction and ascorbic acid and the dietary fiber content (insoluble & soluble), Rhizomes (n=6) of Lasia spinosa were collected from six different markets in the locality near the university. According to the results obtained from the study, Lasia rhizome possessed a wide-ranging antioxidant capacity. A total antioxidant activity of 145.0 - 957.0 umol/g TEAC on a wet weight basis was observed. The contribution from polyphenols to the antioxidant activity ranged from 14% - 48%. In addition to polyphenols, ascorbic acid also contributes to the total antioxidant activity (34% - 56%). The rhizome is a rich source of dietary fiber with 40% - 75% oftotal dietary fiber on dry weight basis, (7.2% - 7.5% on fresh weight basis) constituting 35% - 60% and 4% - 18% of insoluble and soluble fiber respectively. The above antioxidants could act independently or synergistically with fiber, since Lasia spinosa is a rich source of dietary fiber to reduce the adverse effects of various diseases. Thus kohila rhizome can be considered as a valuable functional food from the viewpoint of its antioxidant and dietary fibre content.
Keywords: Lasia spinosa; Antioxidant activity; Polyphenols; Ascorbic acid; Dietary fiber